MANIFESTATION OF WRITING EXPOSITION TEXT TO PROVIDE CONCEPTUAL FACTUAL INFORMATION IN CLASS X STUDENTS IN PASUNDAN INFORMATICS PRIVATE VOCATIONAL SCHOOL - Rika Agustina; Pitriah Maesaroh; Ika Mustika (IKIP Siliwangi, 2019)
Writing exposition text requires ideas that are logically arranged to be clearly expressed and arranged in an interesting manner so that researchers can draw conclusions about the ability of exposition texts to students to be stimulated by using the right method. So that in learning to write exposition text can be responded well by students. This article aims to explain the manifestation of writing exposition text in conveying factual and conceptual information to class X students at Pasundan Public Elementary School, the method used is an experimental method which is a derivative of a descriptive quantitative approach. After conducting in-depth research, it can be concluded that 14% of manifested students have been able to write exposition text by conveying information conceptually, 62% of manifested students have been able to write exposition text by presenting and writing data factually, 18% of students have not been able to write exposition text by conveying information conceptually and 6% of students have not been able to write exposition text by presenting, writing data factually. While the research method used is descriptive quantitative method.